SISTEM KOMUNIKASI PENGEMBANGAN PANGAN LOKAL DI PROVINSI MALUKU (KASUS PANGAN LOKAL ENBAL DI KABUPATEN MALUKU TENGGARA) - Risyart Alberth Far Far; Lydia Maria Ivakdalam; George S J Tomatala (Pattimura Proceeding, 2022)
The people of Southeast Maluku Regency process bitter cassava as household food which is known as "enbal". Enbal is one of the local food resources that can be used as an alternative food ingredient in an effort to diversify food consumption. The purpose of this paper is to analyze the communication system in the development of local enbal food in Southeast Maluku Regency. The results of the study explain that food is an important and strategic commodity for the Indonesian people because it is a basic need that must be met by the government and society together. In developing local food, communication elements in community development must synergize with each other in building local food in order to lead to food self-sufficiency. The government's task in food affairs is to organize, regulate, develop, control and supervise the availability of food, one of which is carried out by issuing policies on food security. The private sector and the community participate in supporting the policy